The business of armaments Armstrongs, Vickers and the international arms trade, 1855-1955 - Spear, Joanna 1961- (Cambridge University Press, 2023)
"This is a study of Britain's most prominent armaments firms and of their relationships with the British Government and foreign states from 1855 to 1955. It reveals how the firms developed and utilised independent domestic strategies and foreign policies against the backdrop of imperial expansion and the two world wars"--